If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -38 = 27 + x Reorder the terms: -38 + 6x = 27 + x Solving -38 + 6x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -38 + 6x + -1x = 27 + x + -1x Combine like terms: 6x + -1x = 5x -38 + 5x = 27 + x + -1x Combine like terms: x + -1x = 0 -38 + 5x = 27 + 0 -38 + 5x = 27 Add '38' to each side of the equation. -38 + 38 + 5x = 27 + 38 Combine like terms: -38 + 38 = 0 0 + 5x = 27 + 38 5x = 27 + 38 Combine like terms: 27 + 38 = 65 5x = 65 Divide each side by '5'. x = 13 Simplifying x = 13
| 10.4=s/5-16 | | 0.8x+2y-2=0 | | 11x-53=55+7x | | 6x=10+8x | | 4x^2-8=31x | | 2+0y=6 | | x/9=-30 | | 9x+21-4x=46 | | 9x-69=99+2x | | 4w+5=20w | | 5(3w-3)+(1+16w)=0 | | 7x^2+6=-23x | | 7x+6x+2x+15=153.75 | | -112+4x=149-5x | | h=5+60t-16t^2 | | -93+2x=94-9x | | 5x^2-6=-1x | | 2x^2-6=-1x | | 7n-5=-19+17n | | x(x^2-5x+4)=0 | | 4-25/6 | | -8+7x=20+5x | | 8(1+2x)=26-2x | | 1x^2-9x=22 | | 1x^2+6x-40=0 | | 0.88-(5.12+0.08y)=4.92-y | | x-8/4=x/6 | | x+0(3)=7 | | 3x+4y-26=0 | | 3-(3x-4)=1+9 | | 5x=20-2x | | 6-2v=14 |